Corona Virus Diseases (COVID-19) and Online Class among Children in Pokhara - Subedi, Netra Prasad (Janapriya Journal of Interdisciplinary Studies, 2020)
The Declaration of COVID 19 as a pandemic became a turning point that shifted the paradigm of human civilization and education system. This paper aims to explore the behavioral aspects of school-level children and the situation of online education after the COVID 19 pandemic in Nepal. The study used an exploratory research design to achieve purposes. The parents having school-level children are the population for this study. And purposive sampling technique is used to collect primary data through an online system by sharing the link of the questionnaire form to parents living in urban areas, and fifty responses collected during a month. Descriptive statistical tools used for analysis purposes. The closure of schools has increased the use of mobiles phone in children. Children spent very little time in house undertakings, indooroutdoor games, singing and dancing, and playing with family members. They have observed changes in their usual behavior, parents are feeling difficulties to handle their children in a house settings. Online education is a new use for Nepalese society and school-level education. The participation of children in online education and the effectiveness is at a satisfactory level. However, electricity, accessory devices, internet facility, the interest of children, and lack of monitoring of children’s education have become the major problems. The study finding suggests that parents should take care of children’s education and prevent them from the unwanted effects of using the mobile phone and other undesirable behavioral changes due to the closures of schools.